On positron annihilation anomalies in ionic crystals - Vorobyev А. А. Alexander Akimovich; Annenkov Yu. M.; Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Vorobev S. A. (1973, 1973)
В фонде НТБ ТПУ отсутствует